A database model for the analysis and assessment of historic timber roof structures. (21st August 2017) - Serafini, A.; Riggio, M.; González-Longo, C.
Abstract : Visual inspection assisted by well-structured forms allows experts to collect homogeneous data in order to report typical damage/vulnerabilities of structures. This is the basis for deriving vulnerability factors to predict failure mechanisms and identify urgent interventions. A database model with an associated structured form for the assessment of historic timber roof structures has been developed during a two-week Short Term Scientific Mission (STSM) in May 2015 at CNR IVALSA Institute in San Michele All'Adige (Italy). The aim is to assist during inspection in recording all the necessary information and later in analysing data from several inspections, allowing to identify typical damage and its causes. The database model, starting from the work of COST Action FP 1101 and further developed and digitalised during the STSM, has been initially populated with data previously collected by the University of Strathclyde through visual assessment of 29 historic timber roofs in Scotland.